1976
DOI: 10.1176/ajp.133.10.1181
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of melatonin on depression

Abstract: In order to test the efficacy of the pineal neurohumor melatonin on depression, the hormone was administered in varying doses to six moderately to severely depressed patients and two patients with Huntington's chorea in double-blind crossover study. Melatonin exacerbated symptoms of dysphoria in these patients, as well as causing a loss of sleep and weight and a drop in oral temperature. Melatonin increased cerebrospinal fluid 5-hydroxyindoleacetic acid and calcium in three of four patients studied. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Regarding evidence assessing melatonin for BD, one open-label study showed no significant effects on mood or sleep in rapid-cycling patients ( 351 ), whereas in another small open-label study it showed sleep-enhancing and antimanic effects in manic patients ( 352 ). As mentioned previously, agomelatine, an agonist of melatonin MT1 and MT2 receptors, has demonstrated preliminary evidence of efficacy in bipolar depression ( 353 ), but agomelatine has other actions on the serotonin system.…”
Section: Effects Of Pharmacotherapy On Mitochondrial Functionsmentioning
confidence: 99%
“…Regarding evidence assessing melatonin for BD, one open-label study showed no significant effects on mood or sleep in rapid-cycling patients ( 351 ), whereas in another small open-label study it showed sleep-enhancing and antimanic effects in manic patients ( 352 ). As mentioned previously, agomelatine, an agonist of melatonin MT1 and MT2 receptors, has demonstrated preliminary evidence of efficacy in bipolar depression ( 353 ), but agomelatine has other actions on the serotonin system.…”
Section: Effects Of Pharmacotherapy On Mitochondrial Functionsmentioning
confidence: 99%
“…Although melatonin is the hormone of the pineal gland, MTNR1A is ubiquitously expressed, predominantly in the suprachiasmatic nucleus, hypothalamus and prefrontal cortex. The melatonin receptor pathway is known to be involved in depression (Carman et al 1976; Wetterberg et al 1984; Goldstein, 1985; Bourin & Prica, 2009; Anderson, 2010; Gałecka et al 2011) and its relationship with somatic complaints, and vitality in general, makes it a biologically plausible gene.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin injections given in the morning stimulate tumour growth, whereas same doses given in the mid-afternoon have no effect but in the evening have a retarding effect [72, 73]. Melatonin administration may unduly prolong the nocturnal melatonin rise or that is given throughout the day may exacerbate bipolar and classic depression [74, 75]. Some people with depression may suffer from a low-melatonin syndrome [76].…”
Section: Negative Effects Of Melatoninmentioning
confidence: 99%